Making of Financial Statements in the Context of Behavioral Accounting - Sri Trisnaningsih; Raci Pitaloka (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to find out how accounting behavior affects financial statements. The research method used is a literature review of articles contained in Google Scholar with keywords searching for accounting articles and financial statements. The so-called users in this case are external parties of the company, such as investors, creditors, and government agencies, while the internal parties of the company are managers and employees of the company. Accounting has an important role as the financial controller of the company and can be used to evaluate and make plans for the future of the company. Accounting must be supported by a good system of conduct from the humans involved in it so that the preparation of accounting reports can be appropriate, relevant, and reasonable. The outcomes of the study determined that accounting conduct has a very important relationship with the composition of relevant and reasonable financial statements so that decision making can be done properly and appropriately and fraud can be avoided.